PLC Based Paint Mixing System - Sivan, Ashish; Bedi, Harpreet (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper explores the transition from manual to fully automated colour production, driven by the increasing demand for high-quality and efficient colour solutions in various industries. By employing mixing tanks and automated processes, the system ensures precise colour mixing in specified proportions, catering to industrial needs. The PLC technologies control, enhancing accuracy and productivity. Additionally, the study compares the effectiveness of traditional manual methods with modern digital approaches, demonstrating comparable results in colour accuracy and quality assurance